The - Blair, John (Oxford University Press, 2000)
John Blair's Very Short Introduction to the Anglo-Saxon Age covers the emergence of the earliest English settlements to the Norman victory in 1066. This book is a brief introduction to the political, social, religious, and cultural history of Anglo-Saxon England and it is the most comprehensive and authoritative short guide to the Anglo-Saxon age available